EFEKTIVITAS PENGGUNAAN INTERACTIVE FLAT PANEL TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP ROUDLOTUS SHOLIHIN KEDALI - Nuroniyah, Khilyatun; Suradji, Muchamad; Halim, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of using Interactive Flat Panel (IFP) on the learning outcomes of seventh grade junior high school students in Islamic Religious Education and Character Education subjects, as well as to determine the improvement of student learning outcomes after the use of Interactive Flat Panel (IFP) in the learning process. The analytical method used in this study was a quantitative method with an experimental design. The research sample consisted of seventh grade junior high school students determined using the total sampling technique. The tests used were Validity Test, Reliability Test, Normality Test, and Wilcoxon Signed Rank Test to determine the effectiveness of using Interactive Flat Panel (IFP) on student learning outcomes. The results of this study indicate that the use of Interactive Flat Panel (IFP) is effective on student learning outcomes. This is evidenced by the increase in post-test scores compared to pre-test scores after the implementation of learning using Interactive Flat Panel (IFP). In addition, the results of the Wilcoxon Signed Rank Test showed a significance value smaller than 0.05, so Ha was accepted and H0 was rejected. Thus, the use of Interactive Flat Panel (IFP) is effective in improving the learning outcomes of seventh grade junior high school students in Islamic Religious Education and Character Education subjects